The blended learning, an educational tool for students in the academic places: A descriptive study - Ghafar, Zanyar Nathir (Yayasan Mitra Persada Nusantara, 2023)
The use of blended learning, a style of education that combines conventional classroom teaching with online learning, is one way in which it is feasible to deliver a course and build a favorable learning environment effectively. A descriptive method by reviewing and critical evaluation of the previously published articles has been used to conduct this research on Blended learning, which combines the conventional in-class education students are used to with the resources they may access online in order to accelerate the learning process and increase students' chances of academic achievement. Aim: This article aims to study the potential benefits of blended learning for students in helping them achieve their academic goals. Many other elements may be considered when creating a practical blended course. When technology is used in the classroom, students have the opportunity to benefit from having quick access to a wide variety of resources, flexibility, effective pedagogy, learner autonomy, an enjoyable atmosphere for learning, involvement with the course materials, immediate feedback, self-evaluation, and additional time to interact with teachers and other students. Overall, adaptable and accessible blended learning is a successful teaching method. The students' motivation and success in the course may also be increased.